M-Learning: Positioning the Academics to the Smart devices in the Connected Future - Tanweer Alam; Mohammed Aljohani (JOIV : International Journal on Informatics Visualization, 2020)
M-learning is about using the massive growth of mobile technologies to benefit learners and learning. As computers and the internet become essential educational tools, the technologies become more portable, affordable, effective and easy to use. Using portable computing devices (such as laptops, tablet PCs, PDAs, and smartphones) with wireless networks enables mobility and mobile learning, allowing college teaching and learning to extend to spaces beyond the traditional classroom. Within the classroom, mobile learning gives university instructors and learners increased flexibility and new opportunities for interaction. Decision support systems can play an important role in decision making for the interaction of instructors and students. Mobile technologies can support learning experiences at the university level that are collaborative, accessible, and integrated with the world beyond the classroom educative learning initiative. In the proposed framework we will use a decision support system for taking some decisions using the system. The system will notify students when they need alert of lecture time, low attendance, meeting time, exam schedule notification, result etc. Also, the Framework will take quizzes periodically for improving the quality of learning of each class and send the result to the student as well as faculty and add this result in the record of the student in university. Students can ask general and technical questions from the system, system reply answer of general questions and send technical questions to the faculty, faculty reply through the system. The student also votes at the end of every lecture, if the system found against vote then send the message to the concerned faculty for improvement in the lecture.  My research will be more helpful for students and university teachers to increase flexibility and interaction with students more effectively.